EFEKTIVITAS REKAYASA TEKNOLOGI RATIONAL EMOTIVE BEHAVIOR THERAPY DAN POSITIVE REINFORCEMENT DALAM MENGURANGI WITHDRAWAL BEHAVIOR ANAK DI SATUAN PELAYANAN PERLINDUNGAN SOSIAL ANAK BANDUNG - KASIH RUSTIANI; Susilawati Susilawati; Ernalia Lia Syaodih (Politeknik Kesejahteraan Sosial Bandung, 2022)
Some of the less than optimal withdrawal handlers are a technological engineering challenge. REPORT THERAPY offered to answer the problem. This therapy is the result of technological engineering that integrates Rational Emotive Behavior Therapy and Positive Reinforcement which is assigned with gradual assignments. REPORT THERAPY aims to change a child's withdrawal behavior by changing irrational beliefs into rational ones and providing positive encouragement to maintain the changing behavior. This study aims to test the effectiveness of REPORT in reducing children's withdrawal behavior. The indicators of withdrawal that were measured were speaking incoherently, panicking, avoiding other people, being alone, lowering the head when walking, and lacking concentration. The research method used is single subject research with A-B-A design. Tests were conducted on 3 children aged 17, 15 and 14 years. This study has a length of observation for 15 days, consisting of 5 days of baseline (A1), 5 days of intervention (B), and 5 days of baseline (A2), and between phases are given a break. The results of this study indicate that REPORT therapy is effective in reducing children's withdrawal behavior. Means withdrawing after therapy decreased from before, with a difference in scores of 20.4, 19.4 and 17, respectively. REPORT therapy can be a reference in handling withdrawal and can contribute to the development of social work practice with children.